Baishouwu Extract Suppresses the Development of Hepatocellular Carcinoma via TLR4/MyD88/NF-κB Pathway - Yong-fang Ding; Zi-xuan Peng; Lan Ding; Yun-ru Peng (Frontiers Media S.A., 2019)
Purpose: The root of Cynanchum auriculatum Royle ex Wight, known as Baishouwu, has been widely used for a tonic supplement since ancient times. The current study was performed to explore the effect of Baishouwu extract on the development of experimental hepatocellular carcinoma (HCC) and the potential mechanism involved.Methods: Rats were injected diethylnitrosamine (DEN) to initiate the multistep hepatocarcinogenesis. Animals were treated concurrently with Baishouwu extract given daily by oral gavage for 20 weeks to evaluate its protective effects. Time series sera and organ samples from each group were collected to evaluate the effect of Baishouwu extract on hepatic carcinogenesis.Results: It was found that Baishouwu extract pretreatment successfully attenuated liver injury induced by DEN, as shown by decreased levels of serum biochemical indicators (AST, ALT, ALP, TP, and T-BIL). Administration of Baishouwu extract inhibited the fibrosis-related index in serum and live tissue, respectively from inflammation stage to HCC stage after DEN treatment. It significantly reduced the incidence and multiplicity of DEN-induced HCC development in a dose-dependent manner. Macroscopic and microscopic features suggested that pretreatment with Baishouwu extract for 20 weeks was effective in inhibiting DEN-induced inflammation, liver fibrosis, and HCC. Furthermore, TLR4 overexpression induced by DEN was decreased by Baishouwu extract, leading to the markedly down-regulated levels of MyD88, TRAF6, NF-κB p65, TGF-β1 and α-SMA in hepatitis, cirrhosis, and hepatocarcinoma.Conclusion: In conclusion, Baishouwu extract exhibited potent effect on the development of HCC by altering TLR4/MyD88/ NF-κB signaling pathway in the sequence of hepatic inflammation-fibrosis-cancer, which provided novel insights into the mechanism of Baishouwu extract as a candidate for the pretreatment of HCC in the future.